Synthesis and optical properties of GdVO4: Eu3+ phosphor. (12th February 2021) - Thakur, Himani; Singh, Rajesh Kumar; Gathania, Arvind K
Abstract: In the present work, we have synthesized GdVO4 doped Eu 3+ using a facile sol-gel method and analysed the effect of concentration variation and annealing temperature on the optical properties. Tetragonal (I41 /amd) zircon type crystal structure of the material was confirmed by x-ray diffraction (XRD) study. The photoluminescence (PL) spectra were recorded with an ultraviolet (UV) excitation of wavelength 325 nm. GdVO4 doped Eu 3+ (1 mol%) gives prominent red emission. This optimized sample was annealed at different temperature and as annealing temperature raises, the crystallinity of the material increases resulting in the improved emission intensity. The emission spectra of this phosphor exhibit intense peaks at wavelengths 593 nm (orange) and 618 nm (red) which corresponds to 5 D0 - 7 F1, 5 D0 - 7 F2 transitions of Eu 3+ ions. 5 D0 - 7 F2, the electric dipole transition is dominant indicating that Eu 3+ ions situated at a non-centrosymmetric site in the crystal structure. GdVO4 : Eu 3+ (1 mol%) annealed at 800 °C gives eminent red emission which can be further used as the potential candidate for bioimaging, lighting, temperature sensing and display devices.